VD_FINDINFO HC / 2014 / 340 vom 15. April 2014 - VD Tribunal cantonal (2014)
ASSISTANCE JUDICIAIRE, AVOCAT D'OFFICE, INDEMNITÉ ÉQUITABLE, AVOCAT, STAGE | 22 al. 2 LPAv, 122 al. 1 let. a CPC (CH), 2 al. 1 RAJ